Psychometric study of the cultural adaptation of the PIUQ in undergraduate students in Lima - Otiura-Trisano, Solange (2024)
Information and communication technologies (ICTs) have played a crucial role in higher education. However, inappropriate use has exacerbated mental health problems. The purpose of this article was to validate the adaptation of the Problematic Internet Use Questionnaire (PIUQ) in young university students from a private university in Lima with 255 students between 17 and 19 years old. Psychometric analysis included exploratory factor analysis (EFA), analysis based on item response theory (IRT) using Samejima’s graded response model, and confirmatory factor analysis (CFA); alpha and omega coefficients were used to assess reliability (internal consistency). The IRT analysis showed adequate discrimination coefficients for all items. The alpha coefficients for each of the three PIUQ-18 subscales were between .7 and .9, and those for the total scale were > .90 (suggesting the possibility of scale reduction). According to the CFA, the original PIUQ-18 model with three factors and a model with a single factor have acceptable fit indicators; however, the EFA suggests the existence of up to four factors with overlap between the control disorder and neglect subscales. The findings led to the proposal of a new reduced scale of nine items with two factors (obsession and neglect, and control disorder) with a better fit, factorial invariance by sex, and adequate internal consistency.